The role of ssc cycle in hockey off-ice training - Sýkora, J.; Franek, V.; Švantner, R. (Slovak Journal of Sport Science, 2021)
The Stretch and shortening cycle (SSC) is one of the most common used mechanism in a human body. The objective of this study was to determine a level of slow and fast stretch-shortening cycle utilization in elite ice hockey players and prescribe some off-ice training recommendations. The sample included 23 professional ice-hockey players of the Slovak Tipos league team HKM Zvolen (2 goalkeepers, 7 defenders, 14 forwards; age 26 ± 4.79 years; height 182.87 ± 6.28 cm; bodyweight 87.22 ± 6.54 kg) in this research. The Depth jump (DJ) test, the Bilateral squat jump test and the Bilateral counter-movement jump test were recorded in order to analyze the players` ability to use fast and slow SSC cycle in lower limbs. The results showed no correlation between DJ and SJ or CMJ tests. However, Pearson correlation revealed strong correlation between SJ and CMJ (p < 0.01, r2 = 0.949). 1 player achieved better score in CMJ test within the range between 10 - 15 % (11.97 %). 16 players scored better in CMJ test than SJ, but the percentage difference was insufficient (from 1.46 to 8.20 %) and finally higher SJ performance than CMJ performance was measured in 6 players (from 0.47 to 16.3 %). 6 players, who don`t utilize SSC efficiently due to their poor tendon stiffness compared to high explosive muscle strength production were instructed to add more plyometric exercises to their training regimen. On the other hand, 16 players were more prone to injury due to insufficient load bearing capacity compared to their ability to generate power. They were instructed to add more maximal strength exercises and strength exercises with emphasis on eccentric phase of movement in order to build the capacity for decelerative movements.